2014
DOI: 10.1177/1420326x14530999
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the indoor air quality in an office operating with natural or mechanical ventilation using short-term intensive pollutant monitoring

Abstract: Building ventilation systems are used to mitigate occupant exposure to airborne pollutants such as particulate matter (PM), carbon dioxide and total volatile organic compounds. Building rating systems such as Leadership in Energy and Environmental Design promote the use of natural ventilation to reduce building energy consumption while improving occupant satisfaction. A number of investigations have attempted to compare indoor air quality (IAQ) between spaces with natural or mechanical ventilation without reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…In agreement, for these two FC ambient PM 10 levels were signi ficantly (p < 0.05) higher (median of 23 and 21 mgm À3 at FC3 and FC4; Table 3S) than those indoors, whereas this was not the case for the FC1 eFC2 that were naturally ventilated. Similarly, previous studies reported higher penetration of outdoor PM through open windows indoors under natural ventilation conditions than when using mechanical ventilations (Montgomery et al, 2015;Loupa et al, 2007 ).…”
Section: Pm 10 and Pm 25 Mass Concentrationsupporting
confidence: 52%
“…In agreement, for these two FC ambient PM 10 levels were signi ficantly (p < 0.05) higher (median of 23 and 21 mgm À3 at FC3 and FC4; Table 3S) than those indoors, whereas this was not the case for the FC1 eFC2 that were naturally ventilated. Similarly, previous studies reported higher penetration of outdoor PM through open windows indoors under natural ventilation conditions than when using mechanical ventilations (Montgomery et al, 2015;Loupa et al, 2007 ).…”
Section: Pm 10 and Pm 25 Mass Concentrationsupporting
confidence: 52%
“…Behaviours such as window opening and closing (Stabile et al 2017), HVAC operation, and walking into or out of a room (Montgomery et al 2015 Many previous experimental studies focused on the separate impacts of occupant behaviors and building performances on the indoor airflow patterns and pollutant diffusion process, such as human movements, air-conditioning system-related parameters and window operation-related natural ventilation (Luo et al 2016;Luongo et al 2016). Several Computational Fluid Dynamics (CFD) models have also been improved by validating with quantitative measurements (Luo et al 2018b;Gosselin and Chen 2008).…”
Section: Introductionmentioning
confidence: 99%
“…19 So, to improve indoor air quality and energy efficiency, many investigators have been working on new advanced ventilation technologies. [20][21][22][23] The control of ventilation by mechanical means in HVAC system can have an important impact on IAQ 24 and energy consumption. 24,25 There is a need for new technologies that can control the ventilation system based on requirements and pollution situation in the building.…”
Section: Introductionmentioning
confidence: 99%